2020
DOI: 10.1021/acsomega.9b02842
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Low-Concentration Arsenite [As(III)] Removal in Single and Multicomponent Systems Using Hybrid Iron Oxide–Biochar Nanocomposite Adsorbents—A Mechanistic Study

Abstract: Rice and wheat husks were converted to biochars by slow pyrolysis (1 h) at 600 °C. Iron oxide rice husk hybrid biochar (RHIOB) and wheat husk hybrid biochar (WHIOB) were synthesized by copyrolysis of FeCl3-impregnated rice or wheat husks at 600 °C. These hybrid sorbents were characterized using X-ray photoelectron spectroscopy, X-ray diffraction, scanning electron microscopy (SEM), SEM–energy-dispersive X-ray spectroscopy, Fourier transform infrared spectroscopy, transmission electron microscopy, physical para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 124 publications
4
35
0
Order By: Relevance
“…Some of these elements were originated from the biomolecules present in L. lucidum leaf extracts that were bound to the surface of AgNPs. The results were almost similar to the previous literature (Kaushal et al, 2019;Singh et al, 2020).…”
Section: Scanning Electron Microscopy and Energy-dispersive X-raysupporting
confidence: 92%
See 1 more Smart Citation
“…Some of these elements were originated from the biomolecules present in L. lucidum leaf extracts that were bound to the surface of AgNPs. The results were almost similar to the previous literature (Kaushal et al, 2019;Singh et al, 2020).…”
Section: Scanning Electron Microscopy and Energy-dispersive X-raysupporting
confidence: 92%
“…SEM images of synthesized Ag-WBC were found to show the spherical morphology of Ag nanoparticles with an average size of 80-100 nm on the surface of WBC (Figure 3B). The EDX spectrum of synthesized Ag-WBC confirms the fact that the composite not only has higher amounts of elemental carbon and oxygen, but it also contains significant quantities of ash elements such as Al, Si, Cl, and Ag as reported in previous studies (Nebojsa et al, 2012;Li et al, 2017;Kaushal et al, 2019;Singh et al, 2020). Some of these elements were originated from the biomolecules present in L. lucidum leaf extracts that were bound to the surface of AgNPs.…”
Section: Scanning Electron Microscopy and Energy-dispersive X-raysupporting
confidence: 83%
“…Arsenic contamination of groundwater is a serious global environmental concern affecting a large number of populations, especially in developing countries. Chronic arsenic toxicity causes severe consequences to human health, such as skin lesions, circulatory and nervous disorders, black foot disease, melanosis, keratosis, non pitting oedema, Bowen’s disease gangrene and cancers of different organs 1 , 2 . Thus, the removal of arsenic from potable water is an essential requirement.…”
Section: Introductionmentioning
confidence: 99%
“…8(b) and (c) display the C 1s spectra of the surface of the SF and TP-SF/Fe samples, and the C 1s XPS spectra are fitted to the absorption peaks at 284.7, 285.7, 286.5 and 288.1 eV, corresponding to the C–C, C–N, C–OH, and O–C O bonds, respectively. 60–62 Furthermore, Fig. 8(d) shows the core-level Fe 2p on the surface of the TP-SF-Fe, and the characteristic peaks are attributed to Fe 2p 3/2 (711.1 eV) and Fe 2p 1/2 (724.5 eV), respectively.…”
Section: Resultsmentioning
confidence: 98%
“…12(b) and (c) , a similar character has been found in the other two dyes (reactive orange GRN and cationic violet X-5BLN) as a function of time. 60 However, it can be observed that as the concentration of the dye solution increases, the final degradation rate gradually reduces. Although for a maximum dye concentration of 80 mg L −1 , the degradation efficiency was the lowest compared with other concentrations, but it still stayed over 91%, 83% and 91%, respectively.…”
Section: Resultsmentioning
confidence: 99%